Desire and laugh: the adorned woman in Aristophanes - Sacconi, Karen Amaral (2020)
Female adornment is an important element in the scenes of seduction, which is present in many genres of the Greek poetic tradition since the Archaic period. This paper considers some of these scenes in Homer and Hesiod and, in this light, aims at analyzing how Aristophanes works with this prototypical scene element in Lysistrata, Assembly of Women and Thesmophoriazusae II (frags. 332, 334 and 337).